Analysis of Student Errors in Solving SPLDV Questions at Suluun Christian High School - Franly Y. Mandagi; Derel F. Kauang; Jorry F. Monoarfa (Departement of Mathematics Education, 2023)
This research aimed to identify the causes of and solutions for student mistakes when tackling SPLDV problems. Descriptive qualitative research describes this kind of study. Data for this study was gathered using tests, interviews, and direct observation. The topic of a set of linear equations in two variables is put to the